Comparison of mid-Cretaceous (Cenomanian–Turonian) high-latitude palynofloras from Patagonia and New Zealand: Richness, ecology, and provincialization - Santamarina, Patricio Emmanuel; Barreda, Viviana Dora; Iglesias, Ari; Varela, Augusto Nicolás; Mays, C. (Palaeogeography, Palaeoclimatology, Palaeoecology)
The Cenomanian–Turonian is considered the warmest interval of the last 150 million years. It was characterized by major disturbances to the global carbon cycle, resulting in elevated pCO2 levels and global temperatures, and witnessed the rise to dominance of angiosperms floras. In this paper, we assess changes of fossil floras during the Cenomanian–Turonian interval based on palynological studies of two distantly-spaced localities in high southern paleolatitudes: the Mata Amarilla Formation of Patagonia, southern South America and the Tupuangi Formation of the Chatham Islands, New Zealand. Richness estimations for each stratigraphic unit and cluster analysis were conducted to assess the vegetation changes. Palynological dominance and the presence/absence of taxa were compiled for these units and compared with others from the Cenomanian of southern Gondwana. We recognize a peak in richness during the Mid-Cenomanian Event in Patagonia, with a fall in richness after the event due to species being displaced by dominant taxa. Several richness peaks are also recognized in New Zealand, but the lack of stratigraphic control prevents correlation with marine-based events. Oceanic Anoxic Event 2 is not recorded in either study area. The inclusion of Gondwanic palynological records demonstrate that the Tupuangi Formation cluster with sites from the Antarctic Peninsula and south-eastern Australia conforming a ‘polar cluster’. However, this area has its own palynological signature, constituting a newly proposed Taxodiaceaepollenites Subprovince. The abundances of key plant groups of the Mata Amarilla Formation cluster with those of Bathurst Island (northern Australia), but also show important differences, likely owing to their geographic separation and latitudinal difference. In summary, our paper presents a new scheme for the mid-Cretaceous palynological provinces of Southern Gondwana and provides novel data sets for Patagonia and New Zealand, which can be used as reference points for palynological and paleoecological ...